Factors influencing Janani Suraksha Yojana utilization in a Northern city of India - Goel, Sonu; Sharma, Deepak; Rani, Soma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Janani Suraksha Yojana (JSY) was launched by Government of India with an objective of increasing institutional delivery. After years of operationalization in the Union territory of Chandigarh, no studies have documented the extent of its utilization and in-turn, effectiveness of its implementation. The aim and objectives of the study was to ascertain the extent of utilization of JSY scheme and to explore the factors influencing its uptake. Methods: It was a community based cross-sectional mixed method concurrent study conducted from August 2012 to March 2014 in Chandigarh city. A total of 100 women residing in the catchment areas of primary and secondary level health care facilities of Chandigarh who gave birth in proceeding two years (2011 and 2012) were interviewed using a structured questionnaire and in-depth interview checklist by trained field investigators. Data analysis was done using SPSS software for windows (version 17). Results: A total of 100 mothers were approached out of which 94 delivered in institution and 34 received JSY benefit. Logistic regression model suggested that more than 3 ANC visits by women was significantly associated with the uptake of JSY benefit (OR= 17.4). The factors influencing decreased uptake of scheme were sub-optimal incentive, delayed payment, problem in arranging for a residence proof and lot of administrative paper work. Conclusions: Though the JSY scheme led to high rate of institutional delivery but the monetary incentive was not availed by most of the beneficiaries. There is a need to remove the bottlenecks and thus ensure smooth delivery of cash benefits.